ENHANCING TECHNOLOGICAL SCIENCE DEVELOPMENT THROUGH MODERN EDUCATIONAL TECHNOLOGIES - Abdullayeva Feruza Samatovna; Qurbonboyeva Sevinch (Journals Park Publishing, 2024)
Technology science plays a crucial role in shaping the future of our society. To fuel its growth and development, it is imperative to employ modern educational technologies that facilitate effective learning and knowledge acquisition. This article explores the potential of integrating modern educational technologies into the field of technology science, highlighting their benefits and discussing various approaches to their implementation. It also emphasizes the importance of fostering a collaborative environment that encourages innovation and multidisciplinary learning. By embracing these advancements, we can enhance the development of technology science and empower the next generation of technologists and scientists.
Keywords: technology science, modern educational technologies, effective learning, knowledge acquisition, immersive learning, virtual reality, augmented reality, personalized learning, adaptive learning, collaborative learning, interdisciplinary approaches, blended learning, gamification, online learning platforms, research and development, continuous professional development, industry-academia collaboration, innovation, technologists, scientists.